NEW TECHNOLOGIES FOR OBTAINING DRY CONSTRUCTION MIXTURES BASED ON DOMESTIC INDUSTRIAL WASTE (Web of Teachers: Inderscience Research, 2025)
This article covers the results of research on obtaining binders for dry building mixtures based on asbestos-cement waste, increasing the hydraulic activity of asbestos-cement waste (ACW), the effect of filler on the physical-mechanical properties of asbestos–cement waste-based binder, the effect of plasticizing additives on the rheological and physical-mechanical properties of dry building mixtures based on asbestos-cement waste, and physical chemical analysis of.